Biomimetic strategy towards gelatin coatings on PET. Effect of protocol on coating stability and cell-interactive properties. Issue 8 (31st January 2019) - Giol, Elena Diana; Van Vlierberghe, Sandra; Unger, Ronald E.; Kersemans, Ken; de Vos, Filip; Kirkpatrick, Charles James; Dubruel, Peter
Abstract : The potential in vascular grafts of gelatin-modified poly(ethylene terephthalate) (PET) was shown herein via their coating stability, ability to promote endothelial cells (ECs) and smooth muscle cells (SMCs) and positive cyto- and endotoxicity assessments. Abstract : Gelatin-modified poly(ethylene terephthalate) (PET) surfaces have been previously realized via an intermediate dopamine coating procedure that resulted in surfaces with superior haemocompatibility compared to unfunctionalized PET. The present study addresses the biocompatibility assessment of these coated PET surfaces. In this context, the stability of the gelatin coating upon exposure to physiological conditions and its cell-interactive properties were investigated. The proposed gelatin–dopamine-PET surfaces showed an increased protein coating stability up to 24 days and promoted the attachment and spreading of both endothelial cells (ECs) and smooth muscle cells (SMCs). In parallel, physisorbed gelatin coatings exhibited similar cell-interactive properties, albeit temporarily, as the coating delaminated within 1 week after cell seeding. Furthermore, no or only minimal immunogenic or inflammatory responses were observed during in vitro cytotoxicity and endotoxicity assessment for all gelatin-modified PET surfaces evaluated. Overall, the combined enhanced biocompatibility reported herein together with the previously proven haemocompatibility show the potential of the gelatin–dopamine-PET surfaces to function as vascular graft candidates.